1980
DOI: 10.1159/000145214
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies on the origin and structure of matrix vesicles in bone of young rats

Abstract: Tibiae of young rats were examined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) in order to study the origin and structure of matrix vesicles in periosteal bone. SEM studies have shown that periosteal osteoblasts have elongated processes with globular structures of 0.1 µm in diameter attached to the cell surface and processes. Similar structures were found to cover the inner surface of osteoblastic lacunae. The SEM studies have further shown that in the periosteal surface (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…The data presented herein support the following conclusions about the structure and function of calcospherulites at the bone mineralization front. First, consistent with previous findings [10], the periosteal mineralization front of the juvenile rat tibial diaphysis exhibited numerous calcospherulites having an average diameter of ~0.5 micron and a Ca/P ratio of 1.3 in situ. Second, these spherulites were shown to actively participate in the mineralization process in vivo since they were intensely labeled with a calcium-binding fluorochrome (calcein) within 24 h after injection into live rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data presented herein support the following conclusions about the structure and function of calcospherulites at the bone mineralization front. First, consistent with previous findings [10], the periosteal mineralization front of the juvenile rat tibial diaphysis exhibited numerous calcospherulites having an average diameter of ~0.5 micron and a Ca/P ratio of 1.3 in situ. Second, these spherulites were shown to actively participate in the mineralization process in vivo since they were intensely labeled with a calcium-binding fluorochrome (calcein) within 24 h after injection into live rats.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been suggested that these structures may represent simultaneous, parallel reactions that exhibit some purposeful or coincidental interaction [4,7]. Relevant to the present study, matrix vesicles and calcospherulites have been observed at the periosteal surface of tibial diaphyses in young rats, and some calcospherulites were reported to be in close contact with the collagen fibers at the mineralization front [10].…”
Section: Introductionsupporting
confidence: 67%
“…Budding from the cell surface [31,32] and cellular degeneration/disintegration [33] are supported by electronmicroscopical studies. Budding and cellular disintegration are the most commonly observed phenomena in the genesis of matrix vesicles of the growth cartilage.…”
Section: Discussionmentioning
confidence: 84%
“…Prior studies have reported the presence of calcified, spherical- or fusiform-shaped structures (calcospherulites) all along the mineralization front of bone [Boyde and Sela, 1978; Sela and Bab, 1979; Ornoy et al, 1980; Aaron et al, 1999]. It has been reported that calcospherulites cluster together during periods of rapid bone formation, and that this focal aggregation is defined by an extracellular matrix assembly of bone acidic glycoprotein-75 [Gorski et al, 2004; Midura et al, 2004].…”
Section: Introductionmentioning
confidence: 99%